al-Taʻlīm al-jāmiʻī al-maftūḥ fī Miṣr : al-nashʼah wa-al-tawajjuhāt al-mustaqbalīyah / taʼlīf Najwá Yūsuf Jamāl al-Dīn. - Jamāl al-Dīn, Najwá Yūsuf. (Maktabat al-Ādāb, 2002)
Open and distance learning; higher education; Egypt; future planning; history; Ph.D. dissertation.